3Dscript: animating 3D/4D microscopy data using a naturallanguage- based syntax. - Palmisano, Ralf; Tripal, Philipp; Schmid, Benjamin; Fraaß, Tina (https://www.quantitativebioimaging.com/qbi2020/conference-and-program-booklet/, 2020)
We introduce a software framework that assembles 3D animations of imaging data using a textual description with a syntax based on natural English language. In contrast to the established key frame based approach, smooth and complex motion sequences are intuitively implemented by concatenating multiple instructions. [1] The syntax is extensible and we demonstrate its integration into existing 3D visualization software. The user typically stores different rendering settings and scene transformations in a number of key frames along a timeline, and the rendering engine creates a smooth animation by interpolating between them. Key frames save the spatial transformation of an object as a state, e.g. three angles for a rotation, and not as a transition. This at least 4 key frames are required to define a 360- degree rotation with constant speed unambiguously. Even more are required if the motion is non-linear, which is essential for achieving smooth and pleasant motions. Software packages therefore typically provide a shortcut to insert key frames for rotations around common axes. More complex motions such as combined rotations around multiple axes, however, are difficult to achieve. The syntax based on natural English language maximizes experience and provides easy access for users of distinct fields. Each instruction is an English sentence. Complex motion sequences are implemented by combining multiple instructions which are applied in the order they appear in the text. The syntax comprises phrases for standard non-linear accelerations, resulting in smooth and natural animations. Self-defined macro functions can be used to define motion and other parameters as functions over time. We provide 3DScript as a Fiji/ImageJ plugin including an hardware-accelerated 3D renderer and a dedicated editor featuring auto-completion and recording. Although tailored to the included rendering engine, both the syntax and our animation framework can be easily adapted by other rendering software.<br
Keywords: 3D Animation; Natural Language Syntax; 3Dscript; Fiji/ImageJ Plug-In

3Dscript: animating 3D/4D microscopy data using a natural-language-based syntax - Schmid, Benjamin; Tripal, Philipp; Fraaß, Tina; Kersten, Christina; Ruder, Barbara; Grüneboom, Anika; Huisken, Jan; Palmisano, Ralf (Nature Methods, 2019)
CRIS-Team WoS Importer:2019-04-09

Brain-wide 3D imaging of neuronal activity in Caenorhabditis elegans with sculpted light. - Schrödel, Tina; Prevedel, Robert; Aumayr, Karin; Zimmer, Manuel; Vaziri, Alipasha (Nature Methods, 2013)
Recent efforts in neuroscience research have been aimed at obtaining detailed anatomical neuronal wiring maps as well as information on how neurons in these networks engage in dynamic activities. Although the entire connectivity map of the nervous system of Caenorhabditis elegans has been known for more than 25 years, this knowledge has not been sufficient to predict all functional connections underlying behavior. To approach this goal, we developed a two-photon technique for brain-wide calcium imaging in C. elegans, using wide-field temporal focusing (WF-TeFo). Pivotal to our results was the use of a nuclear-localized, genetically encoded calcium indicator, NLS-GCaMP5K, that permits unambiguous discrimination of individual neurons within the densely packed head ganglia of C. elegans. We demonstrate near-simultaneous recording of activity of up to 70% of all head neurons. In combination with a lab-on-a-chip device for stimulus delivery, this method provides an enabling platform for establishing functional maps of neuronal networks.

Global brain dynamics embed the motor command sequence of Caenorhabditis elegans. - Kato, Saul; Kaplan, Harris S.; Schrödel, Tina; Skora, Susanne; Lindsay, Theodore H.; Yemini, Eviatar; Lockery, Shawn; Zimmer, Manuel (Cell, 2015)
While isolated motor actions can be correlated with activities of neuronal networks, an unresolved problem is how the brain assembles these activities into organized behaviors like action sequences. Using brain-wide calcium imaging in Caenorhabditis elegans, we show that a large proportion of neurons across the brain share information by engaging in coordinated, dynamical network activity. This brain state evolves on a cycle, each segment of which recruits the activities of different neuronal sub-populations and can be explicitly mapped, on a single trial basis, to the animals' major motor commands. This organization defines the assembly of motor commands into a string of run-and-turn action sequence cycles, including decisions between alternative behaviors. These dynamics serve as a robust scaffold for action selection in response to sensory input. This study shows that the coordination of neuronal activity patterns into global brain dynamics underlies the high-level organization of behavior.

Simultaneous whole-animal 3D imaging of neuronal activity using light-field microscopy. - Prevedel, Robert; Yoon, Young-Gyu; Hoffmann, Maximilian; Pak, Nikita; Wetzstein, Gordon; Kato, Saul; Schrödel, Tina; Raskar, Ramesh; Zimmer, Manuel; Boyden, Edward S.; Vaziri, Alipasha (Nature Methods, 2014)
High-speed, large-scale three-dimensional (3D) imaging of neuronal activity poses a major challenge in neuroscience. Here we demonstrate simultaneous functional imaging of neuronal activity at single-neuron resolution in an entire Caenorhabditis elegans and in larval zebrafish brain. Our technique captures the dynamics of spiking neurons in volumes of ∼700 μm × 700 μm × 200 μm at 20 Hz. Its simplicity makes it an attractive tool for high-speed volumetric calcium imaging.